Silicon Regulates Antioxidant Activities of Crop Plants under Abiotic-Induced Oxidative Stress: A Review - Kim, Yoon-Ha; Khan, Abdul L.; Waqas, Muhammad; Lee, In-Jung (Frontiers in Plant Science, 2017)
Silicon (Si) is the second most abundant element in soil, where its availability to plants can exhilarate to 10% of total dry weight of the plant. Si accumulation/transport occurs in the upward direction, and has been identified in several crop plants. Si application has been known to ameliorate plant growth and development during normal and stressful conditions over past two-decades. During abiotic (salinity, drought, thermal, and heavy metal etc) stress, one of the immediate responses by plant is the generation of reactive oxygen species (ROS), such as singlet oxygen (1O2), superoxide (O2−), hydrogen peroxide (H2O2), and hydroxyl radicals (OH), which cause severe damage to the cell structure, organelles, and functions. To alleviate and repair this damage, plants have developed a complex antioxidant system to maintain homeostasis through non-enzymatic (carotenoids, tocopherols, ascorbate, and glutathione) and enzymatic antioxidants [superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX)]. To this end, the exogenous application of Si has been found to induce stress tolerance by regulating the generation of ROS, reducing electrolytic leakage and malondialdehyde (MDA) contents, and immobilizing and reducing the uptake of toxic ions like Na, under stressful conditions. However, the interaction of Si and plant antioxidant enzyme system remains poorly understood, and further in-depth analyses at the transcriptomic level are needed to understand the mechanisms responsible for the Si-mediated regulation of stress responses.